El Impacto de las nuevas tecnologías en la transformación de los actores políticos. - Martín Granados, Ignacio (2005)
The purpose of this essay is to present the issue of electronic democracy to those who doesn’t know the meaning of the term, by identifying how different political actors are using new information and communication technologies, not only when taking place in the political game, but also in their internal and/or external relationships. Moreover, changes will be raised because of the interaction in traditional politics.